2015
DOI: 10.1259/dmfr.20150019
|View full text |Cite|
|
Sign up to set email alerts
|

To see bruxism: a functional MRI study

Abstract: Objective: Since the pathophysiology of bruxism is not clearly understood, there exists no possible treatment. The aim of this study is to investigate the cerebral activation differences between healthy subjects and patients with bruxism on behalf of possible aetiological factors. Methods: 12 healthy subjects and 12 patients with bruxism, a total of 24 right-handed female subjects (aged 20-27 years) were examined using functional MRI during tooth-clenching and resting tasks. Imaging was performed with 3.0-T MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
1
2
0
1
Order By: Relevance
“…In order to equalize the number of individuals from both groups, data analysis was continued over 12 persons for each group. masticatory muscles is generated from the central nervous system and is supported by the fact that we observed cortical changes between healthy individuals and bruxism patients in clenching function in our preliminary experiment (16). Finding reduced mean percent signal changes in related cortical areas of bruxism patients relative to the same areas of control subjects supported this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In order to equalize the number of individuals from both groups, data analysis was continued over 12 persons for each group. masticatory muscles is generated from the central nervous system and is supported by the fact that we observed cortical changes between healthy individuals and bruxism patients in clenching function in our preliminary experiment (16). Finding reduced mean percent signal changes in related cortical areas of bruxism patients relative to the same areas of control subjects supported this hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…These areas are associated with motor control of the biting force and mediate somatosensory feedback with which tactile proprioception is transferred (23,24). Yılmaz found a similar decreased activation pattern in bruxism patients compared to the control group (16). Additionally, it is reported that these areas play a role in motor attention (25).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, functional magnetic resonance imaging (fMRI) was introduced as an effective tool for non-invasively identifying the anatomical brain areas that are activated by afferent signals. 8 9 …”
Section: Introductionmentioning
confidence: 99%
“…Hirano 등 8,9) 은 저작이 여러 인지 구에 많이 활용되고 있다 12,13) . 구강보건분야에서는 이갈이(bruxism) 와 이악물기(clenching) 시 뇌의 활성부위를 fMRI를 사용하여 확인한 바 있으나 자연스러운 저작 과정 중 뇌 활성을 확인한 연구는 거의 없 다 14,15) . 이에 이 연구를 통해 건강한 대상자의 자연스러운 저작 과정 에서 활성화되는 뇌영역에 대한 기초자료를 확립하고, 저작에 의한 뇌 신경 활성 분석 시 fMRI의 활용성을 검토하고자 한다.…”
Section: 서 론unclassified